Effect of Polycations on Sensitivity of BALB/3T3 Cells to Murine Leukemia and Sarcoma Virus Infectivity - Manning, Jarue S. (1971)
Polybrene or diethylaminoethyl dextran, when added with murine leukemia or sarcoma virus inocula, significantly increased virus infectivity of BALB/3T3 cells. Residual polycation concentrations were nontoxic.